First report of Dermatopelte Erdős & Novicky (Hymenoptera, Eulophidae) from the Indo-Malayan realm, with descriptions of new species - Burks, Roger A.; Yefremova, Zoya A. (Zootaxa, 2015)
Four new species of Dermatopelte Erdős & Novicky (Hymenoptera, Eulophidae), D. bavilucus n. sp., D. collis n. sp., D. hanoica n. sp. and D. heratyi n. sp., are described from the Indo-Malayan biogeographic realm, the first three based on females and the last on a male. While similar to previously described Nearctic and Palearctic species, these new species comprise a distinct species group defined by a stronger transverse pronotal carina and smooth propodeal median panels. The differences between Indo-Malayan, Nearctic, and Palearctic species of Dermatopelte are discussed, and a key to all species of the genus is provided.